Some regularities of distribution of eggs and larvae of the Baltic cod - Grauman, G.B. (Baltijskij Nauchno-issledovatelskij Institut Rybnogo Khozyajstva; "Zvaigzne", 1970)
In the period from 1954 to 1965, quantitative samples on the distribution of eggs and larvae of cod Gadus morhua were collected. It was established that one of the most important reproduction area of cod was the Bornholm Deep (Baltic Sea). The maximum density of eggs was found in the central area of the spawning ground, i. e. above the deep. In the years with elevated oxygen concentration and high salinity, cod eggs distribute at considerable depths but in the stagnation periods the spawning shifts to shallower areas where no oxygen deficiency exists. The dependence between the size of eggs and their vertical distribution exists. In April the main number of eggs is found in the 70-50-meter layer but in June - in the layer from 100 to 70 m. Published Not Known